An in Vitro Study of the Hemostatic Mechanism of the Hibernating Hedgehog - Hjort, Peter F; Eliassen, Einar (Thrombosis and Haemostasis, 1963)
Previous authors have demonstrated that hibernating animals have a prolonged clotting time which is neutralized by protamine. They have concluded — teleologically — that the animals are protected against thrombosis by heparin.We have studied coagulation, fibrinolysis and platelets in hedgehogs before, during and after hibernation:1. Half of the hibernating animals had moderate to very large amounts of a heparin-like anticoagulant. This was the most striking finding, but since it was lacking in half of the animals, it was not necessary for survival.2. The prothrombin time (with hedgehog thromboplastin) increased from 11.1 to 14.1 sec. Factor VII increased, and factors II—X and V decreased slightly. Hibernating animals are probably not vitamin K deficient.3. The recalcification time was prolonged in the hibernating animals, while the cephalin time was not. The Russell viper venom time also appeared to be relatively more prolonged without than with cephalin. Decrease in plasma lipids may be a significant factor during hibernation.4. Fibrinogen decreased moderately. The fibrinolytic activity of the euglobulin fraction was increased during hibernation, but not in all animals.5. The platelet count remained unchanged.6. In hibernating animals there was suggestive evidence of a weak anticoagulant which was not neutralized by Polybrene.7. Cold markedly retards coagulation: the thromboplastin and recalcification times increased 10 times when the temperature decreased from 37° to 4° C.These observations suggest that the hemostatic mechanism changes in a complex manner during hibernation.